A New Method for Verification and Evaluation of PLC Software - Muhammed Ali Nur ÖZ; Özgür Turay KAYMAKÇI (Journal of Innovative Science and Engineering, 2023)
Varying market demands and changes in production standards require production systems to be effortlessly modifiable and quickly operational. On the other hand, designing, developing, and testing the control system of a new production system prove costly and time-consuming. Therefore, most engineers write code intuitively and apply basic and insufficient tests. Moreover, most of the code developed for industrial control systems is still written manually using the ladder programming language. At the same time, almost all code development platforms support users with only manual test interfaces. This causes the testing process to be very long and laborious. In addition, not all possible input and output combinations of the code can be tested most of the time. This is a serious handicap, especially for safety-related systems. This study aims to develop a reusable and quickly implementable method that will accurately translate RTC program and the behavior of RTC in a modular Petri net model. Through this translated model, the system and safety requirements written in the Computation Tree Logic can be verified. An advantage of this method is that it does not require a plant model which makes it reusable for new plants and provides a quick verification method for code written intuitively. A case study is given to demonstrate the correctness of our method.